Kesatuan Bapa dan Putra dalam Tradisi Apostolik (Para Rasul dan Konsili Nisea-Konstantinopel I) - Nugraha, Robertus Bellarminus Aditya Wahyu (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2021)
This paper wants to explain about the unity of the essence of the Father and the Son according to the Apostolic Tradition. Understanding of the unity of the substance of the Father and the Son can be clarified by studying the earliest sources of the Church so that the testimony of that unity becomes stronger. The “Apostolic Tradition” refers to the tradition ofacknowledging the unity of the Father and the Son which is not only shared by the Apostles (as the earliest), but also their future Christian generations (the Church). By capitalizing on the sources of faith that the Church had at the time of the Apostles and the Council of Nicene-Constantinople, the author tries to provide an explanation of the unity of substance, which the Church believes, and is supported by other sources of Church faith. The Church says that Jesus is the word and image of God according to the tradition of the Apostles and that Jesus is of one substance with the Father according to the Council of Nicene and Constantinople I. This means that the Father and the Son are one because the Son is the Word of God and God himself. The Father and the Son are also one because the Son is the most concrete image of God. The Nicene-Constantinople Creed affirms the unity of the Father and Son by acknowledging the oneness of God, rooted in Old Testament divine revelation. Starting from these traditions, the Church has a basis for believing that God is One, at the same time that the Father and the Son are one.